2021
DOI: 10.1111/ecog.05629
|View full text |Cite
|
Sign up to set email alerts
|

Surprising roles of climate in regulating flowering phenology in a subtropical ecosystem

Abstract: Climate-driven changes in phenology have widespread effects on ecological interactions and species' abundances. Most predictions of changes in phenology and the consequences for ecology and conservation are based on research in temperate systems. Climate-driven changes in phenology are largely undocumented in subtropical regions, which host much of the world's biodiversity. Factors important to regulating phenology in temperate systems (e.g. winter chilling requirements) are likely weak or absent in subtropica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 103 publications
(153 reference statements)
3
9
0
Order By: Relevance
“…Our findings add to the growing evidence that warming and chilling temperatures together determine flowering times in subtropical forests (Chen et al., 2017; Du et al., 2019; Song et al., 2021; Von Holle et al., 2010; Wang, Dai, et al., 2015). The divergent responses to spring/summer and fall/winter temperatures would affect the sensitivity to temperature fluctuations in plant species (Cook et al., 2012), leading to differences in interannual variation in flowering times among species.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our findings add to the growing evidence that warming and chilling temperatures together determine flowering times in subtropical forests (Chen et al., 2017; Du et al., 2019; Song et al., 2021; Von Holle et al., 2010; Wang, Dai, et al., 2015). The divergent responses to spring/summer and fall/winter temperatures would affect the sensitivity to temperature fluctuations in plant species (Cook et al., 2012), leading to differences in interannual variation in flowering times among species.…”
Section: Discussionsupporting
confidence: 78%
“…Our results were consistent with a short‐term study in Fushan, which suggested that warmer temperatures in early spring might advance the flowering times of subtropical trees (Wang et al., 2014). Several recent studies also emphasize the importance of spring temperature in structuring spring phenology in subtropical ecosystems (Chen et al., 2017; Park & Schwartz, 2015; Song et al., 2021; Von Holle et al., 2010; Wang, Dai, et al., 2015). The flowering times of several early‐spring flowering species were related to warm temperatures in the previous summer ( N d for mean temperature ≥ 175 days in Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the continuity and integrity of data, the manual records of flowering phenology, including FFD, PFD, and EFD, were selected from the two observation periods (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014). FD (flowering duration) is the length of time between EFD and FFD (Du, Yang, et al, 2019;Song et al, 2021;Wang et al, 2019;Zhang et al, 2015). The data for the years 1996 to 2003 were not included because no data was recorded during this period due to missing observations, and as such post-2014 data are not publicly available at present.…”
Section: Phenological Data Collectionmentioning
confidence: 99%